Manajemen Program Kampung Tertib Lalu Lintas Di Kota Jambi - M. Zidan Qadafi Lubis (PT. Anagata Sembagi Education, 2024)
The traffic order village is a pilot area, in which there are all series in managing safe, smooth and orderly traffic activities, this has the aim that the people in an area can be educated in driving in traffic. The purpose of this study was to find out and explain how the management of the Traffic Control Village Program in Jambi City is. This type of research uses descriptive qualitative methods. The data sources used are primary data and secondary data using data collection techniques through interviews, observation, and documentation. The theory used is the theory of management functions according to George R. Terry, in which there are four aspects of management functions namely, planning, organizing, implementing, and controlling. The results of this study indicate that the management of the Traffic Control Village Program in Jambi City has been going quite well, but there are still some obstacles in carrying out its organizational aspects.